Experiences of ‘traditional’ and ‘one-stop’ MRI-based prostate cancer diagnostic pathways in England: a qualitative study with patients and GPs - Fiona M Walter; Stephanie Archer; Willie Hamilton; Samuel William David Merriel; John McGrath; Alice S Forster; Hashim Uddin Ahmed; David Eldred-Evans (BMJ Open)
Objectives This study aimed to understand and explore patient and general practitioner (GP) experiences of ‘traditional’ and ‘one-stop’ prostate cancer diagnostic pathways in England.Design Qualitative study using semi-structured interviews, analysed using inductive thematic analysisSetting Patients were recruited from National Health Service (NHS) Trusts in London and in Devon; GPs were recruited via National Institute for Health Research (NIHR) Clinical Research Networks. Interviews were conducted in person or via telephone.Participants Patients who had undergone a MRI scan of the prostate as part of their diagnostic work-up for possible prostate cancer, and GPs who had referred at least one patient for possible prostate cancer in the preceding 12 months.Results 22 patients (aged 47–80 years) and 10 GPs (6 female, aged 38–58 years) were interviewed. Patients described three key themes: cancer beliefs in relation to patient’s attitudes towards prostate cancer; communication with their GP and specialist having a significant impact on experience of the pathway and pathway experience being influenced by appointment and test burden. GP interview themes included: the challenges of dealing with imperfect information in the current pathway; managing uncertainty in identifying patients with possible prostate cancer and sharing this uncertainty with them, and other social, cultural and personal contextual influences.Conclusions Patients and GPs reported a range of experiences and views of the current prostate cancer diagnostic pathways in England. Patients valued ‘one-stop’ pathways integrating prostate MRI and diagnostic consultations with specialists over the more traditional approach of several hospital appointments. GPs remain uncertain how best to identify patients needing referral for urgent prostate cancer testing due to the lack of accurate triage and risk assessment strategies.